2019
DOI: 10.1101/gr.239442.118
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression patterns define epigenetic regulators associated with neurological dysfunction

Abstract: Coding variants in epigenetic regulators are emerging as causes of neurological dysfunction and cancer. However, a comprehensive effort to identify disease candidates within the human epigenetic machinery (EM) has not been performed; it is unclear whether features exist that distinguish between variation-intolerant and variation-tolerant EM genes, and between EM genes associated with neurological dysfunction versus cancer. Here, we rigorously define 295 genes with a direct role in epigenetic regulation (writer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 64 publications
4
51
0
Order By: Relevance
“…First, the predicted highly LoF-intolerant genes show a 27.6-fold enrichment for genes heterozygous lethal in mouse (p = 1.03 · 10 −12 ), when compared against those predicted as non-highly LoF-intolerant. Second, they exhibit a 12.7-fold enrichment for transcription factors (p < 2.2 · 10 −16 ), consistent with the known dosage sensitivity of these genes (Jimenez-Sanchez et al, 2001;JG Seidman, C Seidman, 2002;Boukas et al, 2019). Third, they show a total depletion (odds ratio = 0) of olfactory receptor genes (p = 2.5 · 10 −5 ).…”
Section: 5% Of Currently Unascertained Genes In Gnomad Receive Higsupporting
confidence: 53%
See 1 more Smart Citation
“…First, the predicted highly LoF-intolerant genes show a 27.6-fold enrichment for genes heterozygous lethal in mouse (p = 1.03 · 10 −12 ), when compared against those predicted as non-highly LoF-intolerant. Second, they exhibit a 12.7-fold enrichment for transcription factors (p < 2.2 · 10 −16 ), consistent with the known dosage sensitivity of these genes (Jimenez-Sanchez et al, 2001;JG Seidman, C Seidman, 2002;Boukas et al, 2019). Third, they show a total depletion (odds ratio = 0) of olfactory receptor genes (p = 2.5 · 10 −5 ).…”
Section: 5% Of Currently Unascertained Genes In Gnomad Receive Higsupporting
confidence: 53%
“…The fact that taking promoter EZH2 binding into account improves our ability to recognize LoF-intolerant genes on top of CpG density, implies that this mapping can be learned with even greater accuracy by incorporating information about other regulatory factors as well. However, a current barrier to achieving this is the relative paucity of genome-wide binding data across the full repertoire of transcription factors: the human genome encodes approximately 1500 transcription factors (Vaquerizas et al, 2009;Barrera et al, 2016;Lambert et al, 2018) and at least 300 epigenetic regulators (Boukas et al, 2019). In contrast to these numbers, currently ENCODE has profiled only 330 regulatory factors in K562 cells, the most extensively characterized cell line.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed that highly expressed genes tend to be more highly co-expressed (Boukas et al, 2019). Related, differential expression has been shown to confound differential co-expression (Farahbod, Pavlidis, 2019).…”
Section: The Distribution Of Gene-gene Correlations Depend On Gene Exmentioning
confidence: 96%
“…removing the top 4 principal components (PCs). The number 4 was chosen based on our previous analysis (Boukas et al, 2019), where we used positive and negative control genes to assess this. An alternative approach suggested by Parsana et al (2019) is to remove the number of PCs according to the estimated number of surrogate variables using SVA (Leek, Storey, 2007;Leek, Storey, 2008;Leek, Johnson, et al, 2012) with the number of PCs ranging from 10 to 30 in these same tissues -the impact of choosing a different number of PCs will be examined below.…”
Section: The Distribution Of Gene-gene Correlations Depend On Gene Exmentioning
confidence: 99%
See 1 more Smart Citation